Association between TNF-α (-308 A/G, -238 A/G, -857 C/T) polymorphisms and responsiveness to TNF-α blockers in spondyloarthropathy, psoriasis and Crohn's disease: a meta-analysis. (August 2015) - Song, Gwan Gyu; Seo, Young Ho; Kim, Jae-Hoon; Choi, Sung Jae; Ji, Jong Dae; Lee, Young Ho
Aim: The aim of this study is to investigate whether TNF-α polymorphisms are associated with the responsiveness to anti-TNF-α therapy in patients with spondyloarthropathy, psoriasis, and Crohn's disease.Methods: We conducted a meta-analysis on the association between the TNF-α polymorphisms and responsiveness of patients.Results: The meta-analysis indicated an association between the TNF-α -308 G allele (OR = 2.005; 95% CI: 1.417–2.838; p = 8.6 × 10 -5 ), TNF-α -238 G allele (OR = 2.196; 95% CI: 1161–4.154; p = 0.016), and TNF-α -857 C allele (OR = 1.779; 95% CI: 1.130–2.802; p = 0.013) and response to TNF-α blockers in Caucasians.Conclusion: Individuals carrying the TNF-α -308 G, -238 G, or -857 C common alleles show better responses to TNF-α blockers than those with minor alleles in Caucasians.